Reduced alternative insulin dosing in hyperkalemia: A meta‐analysis of effects on hypoglycemia and potassium reduction. Issue 7 (1st June 2021) - Moussavi, Kayvan; Garcia, Joshua; Tellez‐Corrales, Eglis; Fitter, Scott
Abstract: Study Objective: Recent studies have identified that reduced alternative intravenous insulin doses, such as 5 units or 0.1 units/kg, may reduce the risk of hypoglycemia compared to standard doses of 10 units in patients treated for hyperkalemia. However, some studies suggest that these alternative doses may reduce the ability to lower serum potassium. This study was performed to determine the impact of alternative insulin dosing on hypoglycemia and potassium reduction in patients with hyperkalemia. Design: Meta‐analysis. Data Source: PubMed/MEDLINE, CENTRAL, Ovid, and ClinicalTrials.gov were searched from inception through November 2020. Patients: Patients treated with standard (10 units) or alternative (<10 units) insulin dosing strategies for hyperkalemia. Only studies that evaluated hypoglycemia (serum glucose <70 mg/dl), severe hypoglycemia (serum glucose <50 mg/dl), and potassium reduction post‐treatment were included in the meta‐analysis. All articles were assessed for bias using the Cochrane Risk of Bias Assessment Tool and Newcastle‐Ottawa scales for randomized prospective trials and retrospective trials, respectively. Intervention: None. Measurements and Main Results: Ten retrospective cohort studies ( n = 3437) were included and had low‐ or moderate‐risk of bias. Alternative insulin dosing strategies included 5 units, 0.1 units/kg, and <10 units. Alternative dosing had lower pooled odds of hypoglycemia (odds ratio [OR] 0.55, 95% confidence interval [CI] 0.43–0.69, I 2 = 8%) and severe hypoglycemia (OR 0.41, 95% CI 0.27–0.64, I 2 = 0%). No difference in potassium reduction was detected (mean difference −0.02 mmol/L, 95% CI −0.11–0.07, I 2 = 53%). Conclusions: Alternative insulin dosing strategies for hyperkalemia management resulted in less hypoglycemia and severe hypoglycemia without compromising potassium reduction compared to standard dose. Prospective studies are needed to confirm these findings.